A Pengembangan Lembar Aktivitas Siswa Berbasis Penemuan Terbimbing Untuk Meningkatkan Hasil Belajar Matematika di Kelas XI SMA - Harahap, Enni Eria (JURNAL MathEdu (Mathematic Education Journal), 2024)
Purpose of this study is to produce a valid and practical LAS based on guided discovery in trigonometric equations to improve mathematics learning outcomes. This type of research is development research (research and development / R & D) using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. The subjects in this research were students of class XI MIPA SMAS Eria Medan T.A 2023/2024. The data collection instrument consists of learning outcomes tests in the form of essay questions, student response questionnaire sheets and expert validation sheets. The results of the research show that the quality of the LAS developed based on guided discovery in trigonometric equations material is seen from the aspect of its validity. The average score for the LAS assessment from the expert team is 89.8 (valid) and based on the practical aspect with the results of the student response questionnaire using discovery-based LAS. guided is 95.17 (practical) and based on the effectiveness aspect with classical learning completion results, learning indicators, student responses and learning time is 89.46 (effective). The increase in student learning outcomes in the initial test was 47,92 and the final test was 90, resulting in an increase of 42,08. The research results using N - Gain are 0.80 which is included in the high category